Nuclear and magnetic spin structure of the antiferromagnetic triangular lattice compound LiCrTe2 investigated by $$μ ^+$$ μ + SR, neutron and X-ray diffraction - E. Nocerino; C. Witteveen; S. Kobayashi; O. K. Forslund; N. Matsubara; A. Zubayer; F. Mazza; S. Kawaguchi; A. Hoshikawa; I. Umegaki; J. Sugiyama; K. Yoshimura; et al. (Scientific Reports, 2022)
Abstract Two-dimensional (2D) triangular lattice antiferromagnets (2D-TLA) often manifest intriguing physical and technological properties, due to the strong interplay between lattice geometry and electronic properties. The recently synthesized 2-dimensional transition metal dichalcogenide LiCrTe $$_2$$ 2 , being a 2D-TLA, enriched the range of materials which can present such properties. In this work, muon spin rotation ( $$μ ^+$$ μ + SR) and neutron powder diffraction (NPD) have been utilized to reveal the true magnetic nature and ground state of LiCrTe $$_2$$ 2 . From high-resolution NPD the magnetic spin order at base-temperature is not, as previously suggested, helical, but rather collinear antiferromagnetic (AFM) with ferromagnetic (FM) spin coupling within the ab-plane and AFM coupling along the c-axis. The value if the ordered magnetic Cr moment is established as $$μ _{Cr}= 2.36~μ _{B}$$ μ Cr = 2.36 μ B . From detailed $$μ ^+$$ μ + SR measurements we observe an AFM ordering temperature $$T_{N}≈ 125$$ T N ≈ 125 K. This value is remarkably higher than the one previously reported by magnetic bulk measurements. From $$μ ^+$$ μ + SR we are able to extract the magnetic order parameter, whose critical exponent allows us to categorize LiCrTe $$_2$$ 2 in the 3D Heisenberg AFM universality class. Finally, by combining our magnetic studies with high-resolution synchrotron X-ray diffraction (XRD), we find a clear coupling between the nuclear and magnetic spin lattices. This suggests the possibility for a strong magnon–phonon coupling, similar to what has been previously observed in the closely related compound LiCrO $$_2$$ 2 .